Teratogenic Effects of Bisphenol A Exposure During Maternal Pregnancy and Lactation on Developing Rat Pups Testes - Khurshid, Tooba; Ali, Shabana; Ali, Hussain; Bano, Maleeha; Cheema, Hira Waqas; Hussain, Nabiha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the teratogenic effects of Bisphenol A exposure during maternal pregnancy and lactation on the testicular histology of developing rat pups.Design of Study: Laboratory-based experimental study.Place and Duration of Study: Department of Anatomy, Islamic International Medical College Rawalpindi in collaboration with the National Institute of Health (NIH) Islamabad Pakistan from Sep 2018 to Sep 2019.Methodology: Eight weeks old, ten pregnant female rats were divided into groups, each comprising five pregnant rats. Pups were born by spontaneous vaginal delivery. Control group A consisted of 15 male rat pups delivered from 5 pregnant rats, fed on a standard diet during pregnancy and lactation till the 21st day. Experimental group B consisted of 15 male rat pups delivered from 5 pregnant female rats who were administered subcutaneous Bisphenol A at a dose of during their pregnancy and lactation till the 21st day.Results: Significant deterioration of quantitative parameters in testes of the experimental group was seen. The seminiferous tubule diameter in group B was 81.99 ± 10.88 compared to group A which was 111.59 ± 8.36. The germinal epithelial height in group B was 10.47 ± 2.34 compared to 30.41 ± 2.43 in group A. The number of Leydig cells in group B was 17 ± 3.45 compared to 47 ± 4.44 in group A. The number of rounded spermatids in group B was 10 ± 3.74 compared to 38 ± 4.02 in group A.Conclusion: Bisphenol A has teratogenic effects on testicular histology of developing rats............